The importance of the literary text in the teaching of English as an international language - Festino, Cielo Griselda (Todas as Letras - Revista de Língua e Literatura, 2011)
The aim of this paper is to discuss the importance of literary narratives for the teaching of English at a moment when English is associated with all the cultures where it is spoken both as foreign or second language. The literary narrative is foremost in this process because it can be understood as a contact zone that allows both a linguistic and cultural counterpoint.